Identification of an m6A-Related Long Noncoding RNA Risk Model for Predicting Prognosis and Directing Treatments in Patients With Colon Adenocarcinoma - Liao, Wanying; Long, Junyu; Li, Yiran; Xie, Fucun; Xun, Ziyu; Wang, Yanyu; Yang, Xu; Wang, Yunchao; Zhou, Kang; Sang, Xinting; Zhao, Haitao (Frontiers in Cell and Developmental Biology, 2022)
N6-methyladenosine (m6A) and lncRNAs have been implicated in the development of colon cancer, including tumorigenesis, migration, and invasion. However, the specific effect of m6A regulators on lncRNAs is not clear, and m6A-related lncRNAs may be new prognostic biomarkers and may help direct treatment and medication. We identified 29 prognostic m6A-related lncRNAs and constructed a risk model using 12 lncRNAs. The model was an independent prognostic factor and could accurately predict prognosis. A stable and robust nomogram that combined the model and pathologic stage was constructed. A total of 2424 differentially expressed genes (DEGs) were identified based on the model. Functional analysis of the DEGs showed that they were associated with tumour progression, helping investigate the underlying biological functions and signalling pathways of the risk model. In addition, the low-risk group based on the risk model had more sensitivity to afatinib, metformin, and GW.441756, and patients with low risk would more likely respond to immunotherapy. Moreover, patients with higher risk were more sensitive to olaparib, bexarotene, and doxorubicin.